Cloning, expression and immunological characterisation of Coc n 1, the first major allergen from Coconut pollen. (March 2021) - Saha, Bodhisattwa; Karmakar, Bijoya; Bhattacharya, Swati Gupta
Graphical abstract: Highlights: Coc n 1, the first allergen from Coconut pollen belongs to the cupin superfamily. Recombinant Coc n 1 retains allergenicity. Three immunodominant epitopes mapped on the surface of Coc n 1. Coc n 1 is evolutionarily distant from known cupin domain containing allergens. Abstract: Coconut pollen has been documented to be a major contributor to the aeroallergen load in India, causing respiratory allergy in a large cohort of susceptible individuals. Here, we report the identification of the first major allergen from Coconut pollen, Coc n 1. The full-length sequence of the allergen was determined from previously identified peptides and overexpressed in E . coli . Recombinant Coc n 1 folded into a trimer and was found to possess allergenicity equivalent to its natural counterpart. Proteolytic processing of Coc n 1 led to the formation of an immunodominant ∼20 kDa C-terminal subunit and the site of cleavage was determined by amino acid microsequencing. Five linear IgE binding epitopes were predicted and mapped on the homology modelled structure of Coc n 1. Amongst three immunodominant epitopes, two were present towards the C-terminal end. Coc n 1 was found to belong to the highly diverse cupin superfamily and mimics its structure with known 7S globulin or vicilin allergens but lacks sequence similarity. Using sequence similarity networks, Coc n 1 clustered as a separate group containing unannotated cupin domain proteins and did not include known vicilin allergens except Gly m Bd 28 kDa, a Soybean major allergen. 7S globulins are major storage proteins and food allergens, but presence of such protein in pollen grains is reported for the first time. Further study on Coc n 1 may provide insights into its function in pollen grains and also in the development of immunotherapy to Coconut pollen allergy.